Corrosion of Aluminum Alloy in Chloride Medium Containing Pseudomonas aerginosa Bacteria. - Al-Tai, Zuheir T. Khulief (Nahrain University College of Engineering Journal, 2017)
This paper reports the microbiologically induced corrosion (MIC) behavior of aluminum alloy in the chloride medium containing Pseudomonas aerinosa bacteria. MIC studies were performed at room temperature for 15 and 30 day in 2% NaCl electrolyte. System I consisted of 2% NaCl by weight (i.e.,uninoculated) as the control system; system II consists of system I inoculated with Pseudomonas aerinosa bacteria. Corrosion analyses by (Tafel polarization resistance and weight loss method); surface analysis (i.e Microstracture examination; Roughness test and X-Ray diffraction analysis) and microbiologically analyses (i.e Sampling; biofilm formation; isolation and identification) were used in this study. The result of Tafel polarization resistance and weight loss method showed that the bacteria caused increasing of corrosion current and increasing the rate of corrosion compared with system I. Surface analysis showed that the bacteria caused pitting corrosion and increasing the surface roughness compared with system I. The results of microbiologically analyses showed non-uniform and heterogeneous biofilm form on the surface of aluminum alloy after immersion in system II and show the role of Pseudomonas aerinosa bacteria in accelerating pitting corrosion of aluminum alloy in the chloride medium.